COMFORT LEVEL OF GREEN OPEN SPACE IN BANDAR LAMPUNG BASED ON CLIMATE AND HUMIDITY - Azhary Taufiq; Christine Wulandari (Jurnal Belantara, 2022)
Green open space is used as microclimate control in the cities besides its function as a recreational and sports facility for communities. The existence of green open space needed by the community to control and integrity and quality of the environment especially in the city. There was very little research and assessment on green open spaces in Bandar Lampung. The latest research conducted in 2015 about green open spaces showed that only 2,121 ha left in Bandar Lampung. The study aimed to determine the temperature and humidity in the three most visited green open spaces in Bandar Lampung contained Taman Dipangga, Taman Gajah, and Taman Kalpataru. The data were taken in 2019 using the Temperature Humidity Index formula. The results showed that the highest temperature was found in Taman Gajah (34,39 oC), and the lowest was in Taman Kalpataru (27,47 oC). The high temperature in Taman Gajah was due to the lack of shade vegetation in the park. Based on the function of green open space to fill the need of ecological functions, Taman Gajah needs to be improved by adding vegetation with a dense type of canopy density and a variety of cropping patterns to withstand temperature and humidity.